BACK TO COMPETITIVE RUGBY IN THE CONTEXT OF PANDEMIC - P. Velkov (Trakia Journal of Sciences)
This article deals with the feasibility of returning to the competitive performance in the Game in the context of pandemic. The study was performed to assist sport associations in organizing and hosting sport events both on national and international level. It aims at providing guidelines and options that will bring the Game back to its real life, while respecting the standard health requirements and measures.